Ischemic stroke of undetermined source as a priming event for brain metastasis: a case report and systematic literature review - Amisano, Paolo; Ciacciarelli, Antonio; Lorenzano, Svetlana; Berto, Irene; Belcastro, Sara; Toni, Danilo; De Michele, Manuela (Frontiers in Oncology, 2025)
The association between ischemic stroke (IS) and malignancy is well established. Cancer-related strokes are predominantly embolic and classified as embolic strokes of undetermined source (ESUS). While malignancy-associated coagulopathy represents the primary pathogenic mechanism, neoplastic embolization of circulating tumor cells is another potential etiology, particularly in cases of cardiac and pulmonary malignancies. We report the case of a 58-year-old man who presented with ESUS and concurrent multiple pulmonary nodules. Despite a comprehensive oncologic evaluation, including an ultrasound-guided bronchoscopic biopsy of the suspected lesion, no malignancy was detected. Several months later, the patient developed focal seizures, and brain magnetic resonance imaging (MRI) revealed multiple left frontoparietal space-occupying lesions with imaging features suggestive of brain metastases (BMs). A follow-up whole-body computed tomography (CT) scan confirmed a right upper lobe lung mass, which was diagnosed as pulmonary adenocarcinoma on subsequent mediastinal lymph node biopsy. The ischemic event may have contributed to the subsequent development of BMs through neoplastic embolization, allowing malignant cells to proliferate within the ischemic brain parenchyma. Alternatively, the stroke may have resulted from cancer-associated coagulopathy. In this context, post-stroke pathophysiological changes—including blood–brain barrier (BBB) disruption, neuroinflammation, hypoxia-induced angiogenesis, and extracellular matrix (ECM) remodeling—may have created a permissive microenvironment for tumor cell seeding and colonization, definable as a “pre-metastatic niche”. ESUS can be the initial clinical manifestation of an undiagnosed malignancy, and IS itself may facilitate tumor dissemination, ultimately leading to BMs. This case underscores the importance not only of a thorough oncologic workup in patients with ESUS, but also of a strict neuroradiological follow-up, as a delayed diagnosis of cancer-related stroke may allow malignancy progression, significantly worsening the prognosis and limiting therapeutic options.